Un tabú en la sociedad grecorromana: la mujer y el vino - Real Torres, Carolina (Fortunatae: Revista canaria de Filología, Cultura y Humanidades Clásicas, 1995)
Women in Antiquity were valued through their fertility. Thus, the fact that their destiny as wives was determined by their capacity of providing legitimate descendants causes a series of biological, social and ethical factors which ruled their body. This paper is an attempt to draw a reasonable explanation of some features of the behaviour of women in society. It also gives an account of the various kinds of restrictions imposed on them.